IMPLEMENTATION OF THE CLOGS GAME ON THE GROSS MOTOR ABILITIES OF CHILDREN AT AL-FALAH PAUD, PONTANG DISTRICT, AGED 5-6 YEARS REGENCY - Hanis Fuadah; Amat Hidayat; Ibnu Sina (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
The main problem in this research is the underdeveloped gross motor skll of children aged 5-6 years at PAUD Al-Falah, Pontang District. This issue arises due to the limited variety of physical activities and the suboptimal use of educational play tools. This study aims to explore how the implementation of the traditional bakiak game can improve children's gross motor skill., A qualitative approach was used, with data collected through observation, interviews, and documentation. The results show that the bakiak game enhances several aspects of gross motor skills, such as balance, coordination, muscle strength, and agility. Additionally, the activity fosters children's social abilities, including cooperation, discipline, and self confidence. Teachers responded positively, noting that the activity is easy to implement and engaging for children. In conclusion, the bakiak game is effective in supporting the development of gross motor skils in early childhood education settings